Lessons Learned: An Analysis of College Athletic Departments’ 5th-year Scholarship Programs - Lester, John C. (My University, 2014)
Many university athletic departments have instituted scholarship programs that are designed to help student-athletes who have finished their athletic eligibility but have not yet graduated. Often called a 5th-year scholarship, these programs help students with financial aid that is lost when they are no longer playing a sport. An analysis of 11 such programs shows that the success rate of these to be remarkable. Of those studied, the mean graduation rate was 89.9 percent for those students who received a 5th-year scholarship. Compare that graduation rate of 89.9 percent to the university and university athletic department graduation rates, both with a mean of less than 60 percent, and a clear picture emerges about the effectiveness of these 5th-year scholarship programs. This success rate was part of a triumvirate of information that was used to do a policy analysis of 5th-year scholarship programs to evaluate the viability of an institution adding such a scholarship. A second source of data came from surveys of 13 alumni who had graduated after earning one of these 5th-year scholarships. This feedback showed great support for the idea of these scholarships, but did not reveal a clear picture as to how much motivation the scholarships provided for these students to complete college. Most alumni said the scholarship helped their completion efforts, while others said they would have finished one way or another. The third piece of information used for this analysis was interviews with representatives from nine athletic departments with a 5th-year scholarship program. These interviews revealed an overwhelming sentiment that these scholarships were “the right thing to do” and they were an effective tool to help increase graduation rates in the department. The interviews also revealed these 5th-year scholarships may be a unique example of policy diffusion, as the programs appeared to have spread from university to university as others saw or heard about a nearby program that was working. Following Eugene Bardach’s eight-step policy analysis, this program evaluation found these programs appear to be effective because they combine many of the components that experts say make up the best practices recommended today for effective student retention and graduation: financial support, motivated students; monitoring systems for student progress; academic and social support; an institutional priority for academic success; and the creation and enforcement of sanctions for the institution if graduation goals are not met. The analysis suggests the 5th-year scholarships are an effective tool to help students complete college and to help institutions with their retention, progression and graduation efforts. As with many other programs today, funding is a critical consideration, but the rewards appear substantial.
Chapter I: INTRODUCTION - 1 | Background - 1 | Purpose of the study - 2 | Study Outline - 3 | Policy Analysis - 8 | Chapter II: LITERATURE REVIEW - 10 | Introduction - 10 | Student Retention Problems - 11 | Policy Diffusion - 12 | Graduation Rates - 13 | Retention Efforts - 16 | Financial Aid - 20 | Scholarship Impact - 22 | HOPE Scholarship - 23 | Student-athletes - 26 | Conclusion - 28 | Chapter III: METHODOLOGY - 30 | Introduction - 30 | Success Rate Comparisons - 31 | Student Surveys - 36 | Athletic Department Interviews - 39 | Limitations - 41 | Chapter IV: FINDINGS - 43 | Introduction - 43 | Graduation Rates - 43 | Surveys of Graduates - 48 | Athletic Director Interviews and Bardach’s Eight-Step Analysis - 52 | 1. The Problem - 53 | 2. Evidence - 54 | 3. Alternatives - 56 | 4. Criteria - 58 | 5. Outcomes - 62 | 6. Trade-offs - 65 | 7. Decide - 66 | 8. The Full Story - 68 | Summary - 69 | Chapter V: ANALYSIS - 72 | Study Summary - 72 | Findings - 74 | Lessons Learned - 76 | Program Effectiveness - 76 | Incentivizing Success - 78 | Worthwhile Programs? - 80 | Implications - 84 | Future Research - 85 | Summary - 86 | REFERENCES - 88 | APPENDIX A – Summaries of Student Surveys - 95 | APPENDIX B – Protocol Exemption Report - 112 |
Keywords: Public Administration; Retention; College Athletics; Student Athletes; scholarships